Occupational exposure to whole-body vibrations and pregnancy complications: a nationwide cohort study in Sweden. (3rd June 2020) - Skröder, Helena; Pettersson, Hans; Albin, Maria; Gustavsson, Per; Rylander, Lars; Norlén, Filip; Selander, Jenny
Abstract : Objectives: Pregnancy complications are common contributors to perinatal mortality and morbidity. Still, the cause(s) of gestational hypertensive disorders and diabetes are largely unknown. Some occupational exposures have been inconsistently associated with pregnancy complications, but exposure to whole-body vibrations (WBV) has been largely overlooked even though it has been associated with adverse birth outcomes. Therefore, the aim was to assess whether occupational WBV exposure during pregnancy is associated with pregnancy complications in a nationwide, prospective cohort study. Methods: The Fetal Air Pollution Exposure cohort was formed by merging multiple Swedish, national registers containing information on occupation during pregnancy and diagnosis codes, and includes all working women who gave birth between 1994 and 2014 (n=1 091 044). WBV exposure was derived from a job-exposure matrix and was divided into categories (0, 0.1–0.2, 0.3–0.4 and ≥0.5 m/s 2 ). ORs with 95% CIs were calculated using logistic regression adjusted for potential confounders. Results: Among women working full time (n=646 490), we found increased risks of all pregnancy complications in the highest exposure group (≥0.5 m/s 2 ), compared with the lowest. The adjusted ORs were 1.76 (95% CI 1.41 to 2.20), 1.55 (95% CI 1.26 to 1.91) and 1.62 (95% CI 1.07 to 2.46) for preeclampsia, gestational hypertension and gestational diabetes, respectively, and were similar in all sensitivity analyses. There were no clear associations for part-time workers. Conclusions: The results suggest that women should not be exposed to WBV at/above the action limit value of 0.5 m/s 2 (European directive) continuously through pregnancy. However, these results need further confirmation.